Advances in parasitology - Baker, J. R.; Muller, R.; Rollinson, D. (Amsterdam : Academic Press, 2005)
First published in 1963, Advances in Parasitology contains comprehensive and up-to-date reviews in all areas of interest in contemporary parasitology. Advances in Parasitology includes medical studies on parasites of major influence, such as Plasmodium falciparum and Trypanosomes. The series also contains reviews of more traditional areas, such as zoology, taxonomy, and life history, which shape current thinking and applications. Eclectic volumes are supplemented by thematic volumes on various topics including'Remote Sensing and Geographical Information Systems in Epidemiology' and'The Evolution of Parasitism - a phylogenetic persepective'. With an impact factor of 3.9 the series ranks second in the ISI Parasitology subject category.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Parasitology; Parasitic diseases; Parasitic diseases; Parasitology; Electronic books